Surveillance in China's Xinjiang Region: Ethnic Sorting, Coercion, and Inducement. - Leibold, James (Journal of Contemporary China, 2020)
Over the last decade, the Chinese Communist Party has built an unprecedented surveillant assemblage in the Xinjiang Uyghur Autonomous Region (XUAR) with the region's Uyghur Muslim minority as the chief target of augmented Party-state controls. This article interrogates the mechanics, logic and implications of Xinjiang's surveillance society. It demonstrates how Party-state monitoring comes not only in the form of physical monitoring and forced kinship but also automated, technology-driven tools such as GPS tracking, voice and facial recognition technologies, machine learning algorithms, and other software and hardware. The Chinese Party-state employs surveillance to delineate 'correct' thought and behaviour among its citizens, and then persuade (through coercion and inducement) self-alignment with Party and Han-defined norms. The results are fewer spaces for autonomous, bottom-up social mobilization by the Uyghurs and other minorities, the abolition of non-Han cultural, linguistic and religious practices, and the erosion of social trust in Xinjiang society.